Upaya Meningkatkan Prestasi Pembelajaran PAI Kelas V SDN Pengaringan Menggunakan Model Pembelajaran Problem Based Learning (PBL) - Septi Yuli Rahmawati; Titik Fajriyati; Siti Fatimah; Oky Ristya Trisnawati (IAINU Kebumen, 2023)
This study aims to determine the increase in learning outcomes and activities of fifth grade students of Pengaringan Elementary School on the Tarawih Prayer and Tadarus Al-Qur'an materials using the Problem Based Learning (PBL) learning model. This study used a Classroom Action Research design which was conducted in two cycles. Each cycle consists of 4 stages, namely planning, implementation, observation, reflection. Data collection techniques were carried out through test and non-test techniques (observation and interviews). Learning outcomes in the initial conditions, cycle I and cycle II increased. The average learning outcomes in the initial conditions, namely 64, increased in the first cycle to 76, increased again in the second cycle to 80. In the initial conditions, students who completed there were 7 students with a presentation of 38% and 11 students who had not completed with a percentage of 62%. . There was an increase in the first cycle, there were 12 students who finished with a percentage of 77% and 6 students who had not finished with a percentage of 23%. There was an increase again in cycle II, there were 14 students who completed with a percentage of 88% and 4 students who had not completed with a percentage of 12%.